2021
DOI: 10.3390/s21041545
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Physical Activity Patterns across Ages in a Large UK Based Cohort: The UK Biobank Study

Abstract: The ability of individuals to engage in physical activity is a critical component of overall health and quality of life. However, there is a natural decline in physical activity associated with the aging process. Establishing normative trends of physical activity in aging populations is essential to developing public health guidelines and informing clinical perspectives regarding individuals’ levels of physical activity. Beyond overall quantity of physical activity, patterns regarding the timing of activity pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…These included studies into: functional fitness, measured through walking pace [12] or grip strength [13]; cardio vascular disease [14,15] and heart failure [16]; cancer generally [17] and specifically breast cancer [18]; mental health [19] including psychiatric conditions [20,21] and depression and anxiety [22]; mortality generally [23,24], but also concentrating on volume and intensity of activity [25,26]; sleep quality [27,28] and the relationship of sleep to morbidity outcomes [6,29]; and circadian rhythms [30,31]. Outside of health, a range of studies have been reported that correlate these objectively measured physical activity levels with other observations and outcomes such as environmental characteristics [32], travel [33], and activity [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…These included studies into: functional fitness, measured through walking pace [12] or grip strength [13]; cardio vascular disease [14,15] and heart failure [16]; cancer generally [17] and specifically breast cancer [18]; mental health [19] including psychiatric conditions [20,21] and depression and anxiety [22]; mortality generally [23,24], but also concentrating on volume and intensity of activity [25,26]; sleep quality [27,28] and the relationship of sleep to morbidity outcomes [6,29]; and circadian rhythms [30,31]. Outside of health, a range of studies have been reported that correlate these objectively measured physical activity levels with other observations and outcomes such as environmental characteristics [32], travel [33], and activity [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…49,50 A few recent research studies have explored the association between all-cause mortality and diurnal patterns of PA in NHANES 2003-2006 33 or in describing variations for different age group or other medical conditions. [51][52][53] Our finding is among the first to establish an association between daily patterns of PA and long-term cancer survival 54,55,27 after adjusting for age and other confounders, which could be very important for designing time-of-day specific PA interventions.…”
Section: Variablesmentioning
confidence: 69%
“…For example, the 2020/2021 census data in England reported that 24.2% [95% CIs 24 to 24.5] of women were inactive (defined as engaging in less than 30 min of physical activity per week), compared to 22.4% [from 22.4 to 22.6] of men [9]. Furthermore, as age and BMI increases, physical activity levels decline [40,41]. However, this sample does include high educational and SES levels, which are not diverse, and people in national statistics socio-economic classification (NS-SEC) 1-2 are more likely to be active [9].…”
Section: Discussionmentioning
confidence: 99%